Editorial - Minav, Tatiana; Huova, Mikko (International Journal of Fluid Power, 2024)
Welcome to the special issue of the Journal of the International Fluid Power. Most of the papers included here are extended versions of ones presented at the Scandinavian International Conference on Fluid Power (SICFP) conference (Tampere, Finland, 30 May–1 June 2023).